Investigating the Figurative Language of the Novel Entitled "Miles Morales: Spider-Man" by Jason Reynold - Esya Firjatullah Al Hafiz; Maria Yosephin Widarti Lestari; Sri Wahyuni (Lingua Franca, 2023)
The purpose of this study is to (1) investigate the types of figurative language used in the novel Miles Morales: Spider-Man, (2) describe the meaning of figurative language conveyed in Miles Morales: Spider-Man novel, (3) identify what figurative language is used has the most appearances in Miles Morales: Spider-Man novels (4) find out his contribution to education. Researchers used a qualitative descriptive method. The research data is figurative language in a novel entitled "Miles Morales: Spider-Man" by Jason Reynold. Data collection techniques use documentation. At the same time, data analysis is done by identifying figurative language, classification, interpretation, analysis, and conclusion. The study results in mentioning seven figures of speech found in the novel "Miles Morales: Spider-Man" by Jason Reynold, namely metaphor, hyperbole, personification, irony, simile, repetition, and metonymy. The researcher concludes that figurative language has the most appearances in the novel "Miles Morales: Spider-Man" by Jason Reynold.